Genomics of Wolfram Syndrome 1 (WFS1) - Sulev Kõks (Biomolecules, 2023)
Wolfram Syndrome (WFS) is a rare, autosomal, recessive neurogenetic disorder that affects many organ systems. It is characterised by diabetes insipidus, diabetes mellites, optic atrophy, and deafness and, therefore, is also known as DIDMOAD. Nearly 15,000–30,000 people are affected by WFS worldwide, and, on average, patients suffering from WFS die at 30 years of age, usually from central respiratory failure caused by massive brain atrophy. The more prevalent of the two kinds of WFS is WFS1, which is a monogenic disease and caused by the loss of the WFS1 gene, whereas WFS2, which is more uncommon, is caused by mutations in the CISD2 gene. Currently, there is no treatment for WFS1 to increase the life expectancy of patients, and the treatments available do not significantly improve their quality of life. Understanding the genetics and the molecular mechanisms of WFS1 is essential to finding a cure. The inability of conventional medications to treat WFS1 points to the need for innovative strategies that must address the fundamental cause: the deletion of the WFS1 gene that leads to the profound ER stress and disturbances in proteostasis. An important approach here is to understand the mechanism of the cell degeneration after the deletion of the WFS1 gene and to describe the differences in these mechanisms for the different tissues. The studies so far have indicated that remarkable clinical heterogeneity is caused by the variable vulnerability caused by WFS1 mutations, and these differences cannot be attributed solely to the positions of mutations in the WFS1 gene. The present review gives a broader overview of the results from genomic studies on the WFS1 mouse model.